The average rate of change of <em>f(x)</em> on -3 ≤ <em>x</em> ≤ 3 is given to be
(<em>f</em> (3) - <em>f</em> (-3)) / (3 - (-3)) = -2.5
If <em>f</em> (-3) = 14, then
(<em>f</em> (3) - 14) / (3 + 3) = -2.5
(<em>f</em> (3) - 14) / 6 = -2.5
<em>f</em> (3) - 14 = -15
<em>f</em> (3) = -1
Answer:
same
Step-by-step explanation:
The maximum of f(x) is 8 because it's written in vertex notation. From the graph, g(x)'s maximum is 8 so the answer is that they have the same maximum.
Answer:
(3,4)
Step-by-step explanation:
Start at the point (1,1) then Rise 2, and go to the right 3 which will give you the point (3, 4)
In the top right corner is -7x since we multiply the x and -7
In the bottom row, we'll have 5x for the first box and -35 for the second box. Each box is the result of multiplying the outer values.
In the top left corner, the x^2 is from multiplying the two copies of x.
Answer:
-8p ≥ -56
=> p ≤ 7
Step-by-step explanation: